Non-destructive Provenancing of Ground-Edged Mafic Artifacts: A Holocene Case Study from the Sydney Basin, Australia. (4th May 2017) - Attenbrow, Val; Corkill, Tessa; Pogson, Ross; Sutherland, Lin; Grave, Peter
ABSTRACT: Ground-edged artifacts were an important part of the Australian Aboriginal toolkit. They had practical day-to-day uses, but some had symbolic and social values that led to their movement across great distances. Australian provenance studies document long-distance Aboriginal exchange systems extending over hundreds of kilometers. The size and complexity of exchange systems and social networks were contingent upon resources and the productivity of a region's environment. Along the fertile, well-watered lands east of the Great Dividing Range, movement of objects may have been geographically more circumscribed than in drier areas to the west. One hundred and twenty-one mafic, ground-edged artifacts from the New South Wales (NSW) Central Coast and 368 geological specimens from potential sources were non-destructively analyzed by portable X-Ray fluorescence spectrometry. Results indicate the existence of a well-used basalt source within the region at Peats Ridge-Popran Creek as well as multiple local and non-local sources up to 430 km from Mangrove Mountain on the NSW Central Coast.